Creatine supplementation during pulmonary rehabilitation in chronic obstructive pulmonary disease. Issue 7 (1st July 2005) - Fuld, J P; Kilduff, L P; Neder, J A; Pitsiladis, Y; Lean, M E J; Ward, S A; Cotton, M M
Abstract : Background: Skeletal muscle wasting and dysfunction are strong independent predictors of mortality in patients with chronic obstructive pulmonary disease (COPD). Creatine nutritional supplementation produces increased muscle mass and exercise performance in health. A controlled study was performed to look for similar effects in 38 patients with COPD. Methods: Thirty eight patients with COPD (mean (SD) forced expiratory volume in 1 second (FEV1 ) 46 (15)% predicted) were randomised to receive placebo (glucose polymer 40.7 g) or creatine (creatine monohydrate 5.7 g, glucose 35 g) supplements in a double blind trial. After 2 weeks loading (one dose three times daily), patients participated in an outpatient pulmonary rehabilitation programme combined with maintenance (once daily) supplementation. Pulmonary function, body composition, and exercise performance (peripheral muscle strength and endurance, shuttle walking, cycle ergometry) took place at baseline (n = 38), post loading (n = 36), and post rehabilitation (n = 25). Results: No difference was found in whole body exercise performance between the groups: for example, incremental shuttle walk distance mean −23.1 m (95% CI −71.7 to 25.5) post loading and −21.5 m (95% CI −90.6 to 47.7) post rehabilitation. Creatine increased fat-free mass by 1.09 kg (95% CI 0.43 to 1.74) post loading and 1.62 kg (95% CI 0.47 to 2.77) post rehabilitation. Peripheral muscle performance improved: knee extensor strength 4.2 N.m (95% CI 1.4 to 7.1) and endurance 411.1 J (95% CI 129.9 to 692.4) post loading, knee extensor strength 7.3 N.m (95% CI 0.69 to 13.92) and endurance 854.3 J (95% CI 131.3 to 1577.4) post rehabilitation. Creatine improved health status between baseline and post rehabilitation (St George's Respiratory Questionnaire total score −7.7 (95% CI −14.9 to −0.5)). Conclusions: Creatine supplementation led to increases in fat-free mass, peripheral muscle strength and endurance, health status, but not exercise capacity. Creatine may constitute a new ergogenic treatment in COPD.